Metode Sejarah Ibn Khaldun - Saidun Derani (Buletin Al-Turas, 2011)
Ibn Khaldun is a medieval Muslim scholar who was internatonally known for his scientific reputation as well as his pioneered study oof historical writing. this study offers a new method that not only informant (news man), but also on the understanding of each civilization characteristics and the laws of nature (sunnatullah) that go with it iin order for the public to be freed of false information in the history narrative. He also introduced new sciience called the science of al-Umran (al-Ijtima' al-Basyari), wich on the next period developed into a science of sociology, that focuses on cummunity studies.